Exercise Regulates the Metabolic Homeostasis of Methamphetamine Dependence - Xue Li; Kefeng Li; Zhicheng Zhu; Yu Jin; Zhanle Gao; Jisheng Xu; Li Zhang (Metabolites, 2022)
Physical exercise is effective in enhancing cognitive function, reducing anxiety and depressive symptoms, reducing cravings, and improving quality of life in methamphetamine (METH) addiction. However, little is known about the effect of exercise on metabolic profiles. We performed LC/MS-based targeted metabolic profiling on serum samples to investigate the metabolic characteristics of METH dependence and find the differences between METH-dependent individuals and nonusers and evaluated the metabolomic profiles of individuals with METH dependence following aerobic exercise training. We identified a total of 201 metabolites, among which 115 were differentially expressed under METH use. Among the differentially regulated metabolites, 72 were selected as potential biomarkers. Further analysis identified 19 pathways, among which glyoxylate and dicarboxylate metabolism; alanine, aspartate, and glutamate metabolism; and citrate cycle were most significantly affected by METH. The aerobic exercise intervention differentially regulated 55 metabolites, of which 51 were selected as potential biomarkers and were mainly enriched in 10 pathways. Interestingly, alanine, aspartate, and glutamate metabolism and nitrogen metabolism were the remarkably affected pathways. Furthermore, METH increased the serum levels of glutamate and decreased GABA, whereas exercise decreased the serum levels of glutamate and increased GABA. Results suggested that METH dependency disturbed normal metabolic homeostasis, whereas exercise restored metabolism.